ChemInform Abstract: Experimental Determination of the Equilibrium Relationship of Fe—Pd—Pr Ternary System at 773 K. Issue 49 (December 2015) - Du, Y. S.; Li, C. R.; Cheng, G.; Sun, Y. Z.; Wu, X. F.; Li, L.; Rao, G. H.
Abstract: The solid state phase equilibria in the title system are characterized by powder XRD, FESEM, DSC, and EDS.